Health, Physical Education and Sport Sciences University of Tsukuba
Homepage der Universität Tsukuba (Japan) mit einem Überblick über das Lehrangebot und die Forschungsaktivitäten der einzelnen wissenschaftlichen Mitarbeiter "The Institute of Health & Sport Sciences consists of four major research fields; sport and physical education studies (cultural, social, and educational sciences of sports, leisure and physical education), coaching sciences (methodology and coaching sciences for individual sports including outdoor education), health sciences (health education, sports medicine. human anatomy, nutrition etc.), and human performance sciences (exercise physiology, sport biomechanics, exercise biochemistry etc."